2009
DOI: 10.1097/acm.0b013e3181bf51a6
|View full text |Cite
|
Sign up to set email alerts
|

Residents’ and Attending Physicians’ Handoffs: A Systematic Review of the Literature

Abstract: Despite the negative consequences of inadequate physicians' handoffs, very little research has been done to identify best practices. Many of the existing peer-reviewed studies had design or reporting flaws. There is remarkable consistency in the anecdotally suggested strategies; however, there remains a paucity of evidence to support these strategies. Overall, there is a great need for high-quality handoff outcomes studies focused on systems factors, human performance, and the effectiveness of structured proto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
202
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 312 publications
(209 citation statements)
references
References 61 publications
4
202
0
3
Order By: Relevance
“…23,222 However, the concept of 'team' in healthcare is rapidly evolving to include a greater emphasis on interprofessional collaboration, 223 as well as new team structures. With the advent of restricted duty hours, 224 and frequent hand-offs, 29,30 team members are often working in shifts [225][226][227] and are also becoming dispersed geographically. The telemedicine intensive care unit is an example in which intensivists and nurses use telemetry and electronic medical records to provide care to patients hospitalized remotely.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…23,222 However, the concept of 'team' in healthcare is rapidly evolving to include a greater emphasis on interprofessional collaboration, 223 as well as new team structures. With the advent of restricted duty hours, 224 and frequent hand-offs, 29,30 team members are often working in shifts [225][226][227] and are also becoming dispersed geographically. The telemedicine intensive care unit is an example in which intensivists and nurses use telemetry and electronic medical records to provide care to patients hospitalized remotely.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of patient hand-over were excluded since recent reviews on this topic have been published. [29][30][31] Title and Abstract ReviewThe search yielded 12,922 citations (Fig. 1).…”
mentioning
confidence: 99%
“…2,3 Recognizing such findings, a growing body of literature addresses handoff techniques for learners. [4][5][6][7] Vidyarthi described the handoff process as ''traditionally informal, unstructured, and idiosyncratic,'' 4 and many believe efforts to formalize and structure this process are important for patient safety. 8 Standardized handoff forms have improved accuracy of information.…”
mentioning
confidence: 99%
“…Despite widespread awareness of the negative consequences of poor communication in handoffs and transitions of care, little research has identified best practices. 7,48,49 Authors such as Hilligoss and Cohen 50 and Horowitz and colleagues 51 suggest that education for effective handoffs incorporate direct observation and feedback or handoff behaviors, use of reflective practice as a way to inculcate vigilance, and attention to differences in handoff types (for example, within-unit handoffs [between trainees who are largely known to one another] and betweenunit transfers of care [between trainees or attending physicians who are strangers to one another]). We are developing a handover tool for residents and attending physicians 7 have reviewed the literature on handoffs in a number of high reliability industries and concluded that faceto-face handoffs have the highest accuracy and reliability.…”
Section: Discussionmentioning
confidence: 99%